PREDIKSI FINANCIAL DISTRESS DENGAN MENGGUNAKAN PENDEKATAN LOGISTIC REGRESSION (LOGIT) PADA PERUSAHAAN PLASTIK DAN KEMASAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2016 - Siregar, Sabrina Amalia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This research aims at predicting financial distress of plastic and packaging companies listed on Indonesia Stock Exchange using 14 financial ratios. The type of this research is explanatory research, which attempts to explain the causal relationship between variables. The population of this research includes all plastic and packaging companies that were listed on Indonesia Stock Exchange from 2012 to 2016. The sample was determined using purposive sampling technique, hence 10 companies consist of 3 distress companies and 7 non distress companies were obtained. Thereafter, logistic regression analyses were conducted on that sample.Â The results of this research indicate that ROA and TATO partially showed a significant relationship with financial distress on the plastic and packaging companies listed on Indonesia Stock Exchange period 2012 - 2016. The accuracy rates of the proposed prediction model isÂ 90%. Keywords: financial distress, financial ratio, logistic regression